The Bible in Human Transformation : Toward a New Paradigm in Bible Studies - Wink, Walter (Book collections on Project MUSE., 2010)
""Historical biblical criticism is bankrupt."" That startling affirmation began The Bible in Human Transformation when it first appeared in 1975. Wink asserts that despite the valuable contributions of the historical-critical method, we have reached the point where this method is incapable of allowing Scripture to evoke personal and social transformation today. More than thirty years later, Wink now looks back in a new preface over the more and less humanizing developments in New Testament studies of the last few decades and renews his call for a transforming approach to biblical interpretatio